Mężczyzna w rodzinie górali huculskich - Haratyk, Anna (Biuletyn Historii Wychowania, 2012)
Hutsuls as one of the ethnic groups living in the Carpathian mountains have created peculiar culture, distinct from other mountain societies and original in many aspects. The relationships in the socalled typical families were also very characteristic. Dominant role was played by a man. The oldest man in a family was responsible for relationships and rights in the family and for upbringing of children. Men’s amoral behaviour, rooted in tradition, very often contributed to depravity and breakdown of marriages. Men often got married for fortune, were unfaithful to their wives and beat them. Such behaviour was treated in the Hutsul community as a husband’s privilege and duty. The role of a man in the Hutsul family was significant but in many cases negative.